Jednoczesna operacja zaćmy w obojgu oczach – zalety i wady - Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
During the past decade, advances in techniques and technology led to major changes in cataract surgical practice patterns. In this progression towards ever faster eye rehabilitation after surgery, simultaneous bilateral cataract surgery (SBCS) may be the next and ultimate step. It is not routinely performed: however, there are certain situations in which SBCS might be beneficial to the patients. It has been considered a good option in patients who have significant cataract in both eyes and are not good candidates for having anesthesia and surgery twice. The question is, if the benefits by bilateral surgery justify the risk of simultaneous complications, in particular endophthalmitis. In this perspective we present the clinical, social and economic advantages and disadvantages of such surgical procedures.